(untitled) (REMUNOM, 2025)
The objective of this study was to analyze the influence of organizational culture on the management of accounting business models. To this end, three specific objectives were defined: to characterize the management present in the offices analyzed, to identify the cultural dimensions that influence these organizations, and to propose an alignment between current management and the cultural perceptions identified. The research, of a descriptive and qualitative nature, was conducted through four cases, with different business models (two traditional and two digital). Seventeen questions based on cultural dimensions were analyzed, applied to the employees of the organizations through a questionnaire, in addition to management practices reported by managers through semi-structured interviews. The data were tabulated and interpreted through frequency analysis and categorization. The main results indicated that organizational culture significantly influences the management of accounting business models. In traditional models, there is a focus on standards and stability, while digital models prioritize innovation and flexibility. Cultural dimensions, such as control and openness, shape organizational practices and decisions. In the proposed alignment, it was recommended that traditional models adopt greater flexibility and inclusion, and digital models strengthen governance practices and formal recognition. The study contributes to the understanding of how to align management practices with cultural dimensions, promoting organizational efficiency and adaptability, especially in a sector undergoing transformation such as accounting.